Tetrasomy of 11q13.4-q14.3 due to an intrachromosomal triplication associated with paternal uniparental isodisomy for 11q14.3-qter, intrauterine growth restriction, developmental delay, corpus callosum dysgenesis, microcephaly, congenital heart defects and facial dysmorphism - Chih-Ping Chen; Shuan-Pei Lin; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Fang-Tzu Wu; Dai-Dyi Town; Wayseen Wang (Elsevier, 2021)
Objective: We present tetrasomy of 11q13.4-q14.3 due to an intrachromosomal triplication associated with paternal isodisomy of uniparental disomy (iso-UPD) for 11q14.3-qter and multiple abnormalities. Case report: A 30-year-old primigravid woman was found to have intrauterine growth restriction (IUGR) in the fetus since 28 weeks of gestation, and a 2056-g baby was delivered at 38 weeks of gestation with fetal distress. The baby postnatally manifested hypotonia, microcephaly, facial dysmorphism of micrognathia, retrognathia and low-set ears, ventricular septal defect, atrial septal defect, tricuspid regurgitation and corpus callosum dysgenesis. A single nucleotide polymorphism (SNP) array comparative genomic hybridization analysis on the DNA extracted from the peripheral blood revealed the result of arr 11q13.4q14.3 (71,567,724-89,547,851) × 4, arr 11q14.3q25 (89,466,484-134,942,626) hmz [GRCh37 (hg19)] with a 17.980-Mb triplication of 11q13.4-q14.3 encompassing the genes of GRM5 and MAP6, and loss of heterozygosity for a 45.476-Mb region of 11q14.3-qter consistent with iso-UPD for 11q14.3-qter. Polymorphic DNA marker analysis confirmed paternal iso-UPD for 11q14.3-qter. Cytogenetic analysis of the blood revealed a karyotype of 46,XY,trp(11) (q13.4q14.3). The parental karyotypes were normal. When follow-ups at age 2 years, the neonate manifested physical and psychomotor developmental delay and intellectual disability. Conclusion: Tetrasomy 11q13.4-q14.3 may present the phenotype of IUGR, developmental delay, corpus callosum dysgenesis, microcephaly, congenital heart defects and facial dysmorphism.